Attraction of ugliness. A grotesque body in the poetry of Jan Andrzej Morsztyn - Pfeifer, Kasper (Colloquia Litteraria, 2019)
The aim of this article is to explicate relationships between the concepts of beauty, ugliness and grotesque as well as the category of a grotesque body in the poetry of Jan Andrzej Morsztyn. The author indicates the sources of grotesque performances, ways of their poetic implementation, and attempts to contextualize Morsztyn’s grotesque images in the literary tradition. Wolfgang Kayser’, Michail Bachtin’s and Mieczysław Wallis’s studies constitute theoretical background of the paper.